Progressive collapse analysis on multicore computers using nonlinear dynamic approach - Sergiy Fialko (Computer Assisted Methods in Engineering and Science)
A method for solving the problem of structural progressive destruction is proposed, based on nonlinear finite element dynamic analysis, taking into account both physical and geometrical nonlinearity. Unlike most existing approaches, a specialized method has been implemented to simulate the sudden removal of groups of finite elements at given times, which makes it possible to simulate not only the removal of columns but also fragments of load-bearing walls and staircase-elevator blocks. The proposed approach involves the numerical integration of the Cauchy problem using an implicit method of the predictor-corrector type, with multithreaded parallelization of all key algorithms to accelerate the solution. The reliability of the numerical results is substantiated by comparison with the experimental results presented in other studies. The behavior of realistic structural models with bearing walls as well as without them, consisting of exclusively nonlinear finite elements, under the sudden removal of a fragment of a staircase-elevator block, is studied.